From blemishness to pathology: reflections on a case of alopecia - Magro, Valerio Massimo (Aesthetic Medicine, 2024)
Alopecia areata is an organ-specific autoimmune disorder that targets anagen phase hair follicles. Taking charge of a patient with this problem is a recurring task by both dermatologists and aesthetic physicians. Less frequently, this problem may be brought to the attention of a general practitioner, internist, or endocrinologist. The immune system recognizes autologous constituents of the organism, triggering immunological responses that cause different, even multiple, pathologies in an individual. Alopecia, a complex condition represents a serious imperfection but can sometimes be a sign of autoimmunity. We present a clinical case that has come to our attention, the study of which allows us to underline the potential connection of this disease with many other autoimmune pathologies, as well as serious ones, which in the adult subject must be investigated for the purpose of early diagnosis and prompt intervention, not only aesthetic purposes.